Molecular characterization and expression analysis of hypoxia inducible factor-1α during hypoxic stress in speckled blue grouper (Epinephelus cyanopodus) - Along Gao; Qiaoyi Chen; Yukun Huang; Zhiya Yu; Wenjie He; Jinhui Wu; Jinxiong Huang; Tiangaung Cai; Hu Shu (Frontiers in Marine Science)
The speckled blue grouper (Epinephelus cyanopodus) is a coral reef-dwelling grouper with high market and ecological value. During intensive aquaculture and the transportation of live fish, fish often expose acute hypoxic stress. In this study, transcriptomic techniques were used to detect the response of E. cyanopodus to acute hypoxia. The results showed that after acute hypoxia, there were 2,887 differentially expressed genes (DEGs) in the head kidney. GO and KEGG enrichment analyses revealed that the DEGs were mainly involved in processes such as transmembrane signal receptor activity, G protein-coupled receptor activity, and molecular transducer activity, involving the HIF-1, PI3K-Akt, and AMPK signaling pathways. In addition, E. cyanopodus HIF-1α (EcHIF-1α) was cloned and characterized. Multiple analyses have shown that the EcHIF-1α had a relatively high conservation. Tissue distribution indicated that EcHIF-1α was expressed in all tissues and was highly expressed in the heart, liver, and peripheral blood. The results of qRT-PCR were consistent with the transcriptomic techniques, and the expression of EcHIF-1α was significant after hypoxia. Meanwhile, EcHIF-1α was significantly induced by Vibrio harveyi, LPS and Poly (I:C) in the head kidney and liver, indicating that EcHIF-1α was involved in the immune response. After hypoxia treatment, the significant expression of EcHIF-1α induced by Vibrio harveyi, LPS and Poly(I:C) was further advanced and enhanced. These results not only confirmed the key role of HIF-1α in fish pathogen infection, but also demonstrated experimentally for the first time that oxygen stress can pre-activate the immune response of speckled blue grouper against pathogenic bacteria. Overall, the work not only contributes to a thorough understanding of the hypoxia tolerance mechanism of teleost, but also provides a new perspective for further exploration of hypoxia and the outbreak of aquatic pathogen diseases.